2012
DOI: 10.1136/eb-2012-100537
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the accuracy of clinical decisions based on full-text articles and on journal abstracts alone: a study among residents in a tertiary care hospital

Abstract: BackgroundMany clinicians depend solely on journal abstracts to guide clinical decisions.ObjectivesThis study aims to determine if there are differences in the accuracy of responses to simulated cases between resident physicians provided with an abstract only and those with full-text articles. It also attempts to describe their information-seeking behaviour.MethodsSeventy-seven resident physicians from four specialty departments of a tertiary care hospital completed a paper-based questionnaire with clinical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…To be most useful, current clinical evidence needs to be conveniently accessible 45. When provided access to either abstracts or full-text articles, improvements in clinical decisions have been observed 3. With a high percentage of clinicians (69%) using abstracts only in seeking answers to clinical questions,3 it is crucial that a high standard of quality for published abstracts is present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To be most useful, current clinical evidence needs to be conveniently accessible 45. When provided access to either abstracts or full-text articles, improvements in clinical decisions have been observed 3. With a high percentage of clinicians (69%) using abstracts only in seeking answers to clinical questions,3 it is crucial that a high standard of quality for published abstracts is present.…”
Section: Discussionmentioning
confidence: 99%
“…When provided access to either abstracts or full-text articles, improvements in clinical decisions have been observed 3. With a high percentage of clinicians (69%) using abstracts only in seeking answers to clinical questions,3 it is crucial that a high standard of quality for published abstracts is present. A 10-year follow-up study found that using structured abstracts, regardless of precise formats, has helped maintain a high quality of available abstracts 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further critical to write an abstract that contains a concise summary of the study design. The importance of an abstract that conforms to CONSORT cannot be overestimated, as the abstract of a paper is the most publicly accessible component of the manuscript after the title; may be all that is read after the title (Barry, Ebell, Shaughnessy, Slawson, & Nietzke, 2001;Fontelo, 2011;Haynes et al, 1990;Marcelo et al, 2013;Saint et al, 2000); and major search engines including PubMed and Google Scholar both focus on title and abstract rather than full text. An official CONSORT extension specific to reporting of both article and conference abstracts has been published (Hopewell et al, 2008).…”
Section: Title and Abstractmentioning
confidence: 99%
“…These aspects are to be taken into account when practising evidence-based medicine for the best approach to medical decision-making. The concept of EBM , as described above, is to translate the need of physicians for information into answerable questions to track down the best information used to answer those questions 13 14…”
Section: Introductionmentioning
confidence: 99%